Experimental Tests on Steel Plate-to-Plate Splices Bonded by C-FRPS Laminas with and without Wrapping - Mario D’Aniello (Technologies, 2016)
The results of an experimental investigation carried out on steel splices bonded by (Carbon-Fiber–Reinforced Polymers) C-FRPs are presented in this paper. The main aim of the study is to examine the influence of different parameters on the type of failure and on the ductility of splices. Different configurations of the specimens were considered, including butt and lapped joints using different arrangements for end anchorage of the bonded C-FRP laminas, such as (i) external bonding; and (ii) anchored jacketing with C-FRP sheets transversally wrapped to the longitudinal axis of the joints. The results in terms of failure modes and response curves are described and discussed, highlighting the potentiality of these types of bonded connections for metal structures. In particular, experimental results showed that (i) the failure modes exhibited by both butt and lapped wrapped splices were substantially similar; (ii) the wrapped anchoring is beneficial in order to achieve large deformations prior to failure, thus allowing a satisfactory ductility, even though a more timely installation process is necessary.